A prospective randomized study on the benefits of a new small-caliber colonoscope - Sato, K.; Ito, S.; Shigiyama, F.; Kitagawa, T.; Hirahata, K.; Tominaga, K.; Maetani, I. (Endoscopy, 2012)
Background and study aims: We compared the performance efficiency of a newly developed small-caliber colonoscope (PCF-PQ260 L) with passive bending, high force transmission, and an outer diameter of 9.2 mm with that of a standard colonoscope, in female and male patients, particularly with regard to passage through acute angulations or into the proximal colon. Patients and methods: A total of 330 patients were randomly allocated to undergo small-caliber (n = 164) or standard (n = 166) colonoscopy. The patients were assessed for pain using a visual analogue scale (0 = none, 100 = extremely painful), and for cecal intubation, withdrawal time, difficulty of colonoscopy, dosage and level of sedation used, and any complications.Results: Median maximum pain and overall pain during colonoscopy were significantly lower in the small-caliber group than in the standard group in women (25 vs. 45, P < 0.001 and 15 vs. 26, P = 0.001, respectively), whereas no significant differences were seen in men (8 vs. 10, P = 0.103 and 16 vs. 20, P = 0.166, respectively). Furthermore, no significant differences were seen between groups in cecal intubation rate or time to cecum in all patients or by sex. Conclusions: Use of the small-caliber colonoscope reduced pain in female patients, but offered no advantage over standard colonoscopy in male patients. The performance of the small-caliber colonoscope was equivalent to that of the standard colonoscope in terms of cecal intubation rate and time to cecum, regardless of the sex of the patient.